2019
DOI: 10.1097/eja.0000000000001058
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial labour analgesia is associated with a reduced risk of maternal depression at 2 years after childbirth

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 48 publications
(64 reference statements)
0
50
0
1
Order By: Relevance
“…Several lines of evidence have suggested that the risk of postpartum depression is reduced in women who receive epidural analgesia, compared with those without analgesia [22,23]. Liu et al reported that the use of neuraxial analgesia during labor was associated with a reduced risk of postpartum depression at two years after delivery [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence have suggested that the risk of postpartum depression is reduced in women who receive epidural analgesia, compared with those without analgesia [22,23]. Liu et al reported that the use of neuraxial analgesia during labor was associated with a reduced risk of postpartum depression at two years after delivery [9].…”
Section: Discussionmentioning
confidence: 99%
“…Severe labor pains are a risk factor of postpartum depression in pregnant women, and early depression is associated with an increased risk of long-term depression [9]. Postpartum depression affects women who have given birth and is a common disorder for new mothers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also reported by Suhitharan et al [ 18 ] in a case-controlled study, that is, the absence of ELA was an independent risk factor for the development of postpartum depression. Furthermore, a recent study of Liu et al [ 19 ] showed that the use of neuraxial analgesia during labor was associated with a reduced risk of maternal depression at 2 years after childbirth.…”
Section: Ela Postpartum Depression and Children's Neurodevelopmentmentioning
confidence: 99%
“…[ 15 , 16 ] Recent studies suggest that its use is associated with reduced risks of postpartum depression [ 17 , 18 ] and even long-term depression. [ 19 ] Furthermore, ELA may also affect neonates and children, including neonatal status, [ 20 22 ] breast-feeding, [ 23 25 ] and long-term neurodevelopment; [ 26 , 27 ] but results are conflicting in this aspect. The purpose of this review is to summarize the evidences related to the influences of ELA on the outcomes of neonates and children.…”
Section: Introductionmentioning
confidence: 99%